Liminaridade e exclusão: os catadores de materiais recicláveis e suas relações com a sociedade brasileira - Beatriz Judice Magalhaes (2012)
This work examines the relations between pickers and Brazilian society through three foci of analysis: a set of interviews with pickers in different situations, in Belo Horizonte and its surroundings; two documentaries about pickers Boca de Lixo (Eduardo Coutinho, 1992) and Waste Land (Lucy Walker, 2009); interactions with policy makers and representatives of business sectors and non-governmental organizations. These situations are addressed, respectively, in Chapters 1, 2 and 3 of the dissertation. Taking into account important events such as the creation of the MNCR (Pickers`s National Movement of Recyclable Materials) in 2001, the approval of LNRS (National Solid Waste Act) in 2010, and in recent decades, the rise of environmental issues in the speeches of some sectors of society, the work also discusses the possibility of positive changes in the relationship between waste pickers and society, considering its historical characterization by liminarity (as proposed by Victor Turner) and exclusion.